QUALITATIVE INTERVIEW WITH SENSITIVE PARTIPANTS - Rosaria Indah (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2022)
Background: Interview is the most frequent data collection method utilized in qualitative research. It is used to explore perceptions and/or life experiences of participants related to a particular research topic. When a research investigates a traumatic topic, participants may show sensitive reactions. However, there is scant literature talks about these reactions and how researchers dealt with them, especially in Indonesian context. This case study aims to discuss the author’s experiences interviewing sensitive participants and ways she overcame dilemmas of stopping the interview or continuing it with caution.Case discussion: The case study draws on reflective practices during interviewing 21 disaster-affected participants in a larger ethnographic study exploring medical education in Aceh, Indonesia, inspired by methodological memos written during data collection processes. Sensitive participants may offer three sensitive reactions: 1) Refuse to do interview, 2) regret the interview after revealing many traumatic experiences, 3) show negative symptoms such as crying during the interview. In dealing with these sensitive reactions, researchers may implement strategies, such as  1) conducting interview at a proper time, 2) avoiding ‘normalization’, 3) putting emotion provoking questions at the last part of an interview, 4) applying communication approaches, such as CARE communication dan 3L actions (Look, Listen, and Link), 5) offering participants some alternative ways to do interviews.Conclusion: The findings suggest researchers exploring traumatic topics to prepare themselves with various interpersonal communication skills that are useful in showing acceptance toward sensitive reactions of their participants.